High-temperature fatigue damage mechanism and strength prediction of vermicular graphite iron. (March 2023) - Chen, Y.; Pang, J.C.; Zou, C.L.; Li, S.X.; Zhang, Z.F.
Highlights: Pearlitic vermicular graphite iron has higher strengths. The coupling effects of oxidation and fatigue were analyzed. A new high-temperature fatigue strength prediction model was proposed. Abstract: The high-temperature tensile properties, high-cycle fatigue properties and related damage mechanisms of vermicular graphite iron (VGI) with different microstructures at 500 °C were investigated. It is found that compared with ferritic VGI, pearlitic VGI has higher tensile strength and fatigue strength. The tensile strength shows a linear increasing trend with the increase of pearlite content. For ferritic VGI, fatigue cracks initiate at the graphite/ferrite interface, the ferrite grain boundary softens at high temperature, and cracks propagate along the grain boundary. In pearlitic VGI, fatigue cracks can also initiate at the graphite/pearlite interface due to oxidative debonding, and oxidation accelerates the initiation and propagation of fatigue cracks. Considering the influence of microstructures and temperature, a new method for predicting the high-temperature fatigue strength of VGI was proposed. This method has high prediction accuracy and suits for VGI from the room temperature to the high-temperature.